Low-Dose Radiation Therapy Versus Conventional Physiotherapy in Osteoarthritis Patients: A Comprehensive Systematic Review and Meta-Analysis Evaluating Symptomatic Efficacy and Disease Progression - Gilang Pramanayudha (The International Journal of Medical Science and Health Research, 2026)
INTRODUCTION: Osteoarthritis (OA) constitutes the most prevalent degenerative joint disease worldwide, imposing a profound burden of chronic pain, functional limitation, and disability on the aging population. Conventional physiotherapy serves as the established cornerstone of conservative management, primarily targeting biomechanical optimization and symptom control. Concurrently, Low-Dose Radiation Therapy (LDRT) has experienced a significant clinical resurgence as a non-pharmacological intervention hypothesized to modulate synovial inflammation and halt structural disease progression. However, high-quality clinical evidence remains profoundly contested and polarized. The objective of this comprehensive systematic review is to rigorously evaluate the comparative efficacy of LDRT versus conventional physiotherapy and sham treatments, specifically focusing on the resolution of symptomatic complaints and the alteration of disease progression in OA patients. METHODS: A comprehensive systematic review protocol was executed in strict alignment with PRISMA guidelines. Efficacy data, adverse event rates, and radiological/clinical progression metrics were systematically extracted from peer-reviewed databases and recent oncological and rheumatological trial registries up to the year 2025. The risk of bias was appraised utilizing the Cochrane Risk of Bias 2 (RoB 2) tool. The statistical analysis isolated standardized mean differences (SMD), hazard ratios (HR), relative risks (RR), and confidence intervals (CI) to quantify treatment effects, categorizing findings into symptomatic efficacy, disease progression, and safety profiles. RESULTS: The systematic synthesis integrated diverse trial archetypes, encompassing over 3,000 cumulative patients across multiple cohorts. Conventional physiotherapy demonstrated consistent, short-term efficacy in functional restoration (SMD – 0,166, 95% CI -0,422 to 0.088) and pain reduction (SMD -0.175). Conversely, the most recent 2025 meta-analysis indicates that LDRT yields no statistically significant symptomatic benefit over sham interventions globally (SMD -0.92, P = 0.13). However, modern stratified trials, such as the ASTRO 2025 randomized controlled trial, revealed that a specific 3.0 Gy LDRT regimen yielded significant responder advantages over sham treatments (70.3% vs 41.7%, P=0.014). Most crucially, decade-long longitudinal data indicate that LDRT significantly reduces the hazard of profound clinical disability (Adjusted HR 0.24, 95% CI 0.11 to 0.48) and decreases the incidence of total joint arthroplasty (HR 0.60). Adverse events were measurably higher in LDRT cohorts (RR 1.44). DISCUSSION: The dichotomy in LDRT outcomes points to a highly complex interplay between radiobiological dose thresholds and the profound placebo responses documented in sham-controlled arms. Biologically, LDRT upregulates the Nrf2 antioxidant response, downregulates inducible nitric oxide synthase (iNOS), and polarizes macrophages toward the anti-inflammatory M2 phenotype, effectively arresting the osteoimmunological cascades that drive joint destruction. Physiotherapy remains universally effective for muscular and functional preservation, while LDRT's utility appears tightly restricted to delaying structural progression and end-stage disability in select demographics. CONCLUSION: Conventional physiotherapy maintains its mandate as the primary, biologically safe, and effective first-line intervention for OA. LDRT presents a potent but highly debated alternative that effectively alters long-term disease progression and disability trajectories but carries a measurable increase in localized adverse events and oncogenic risk. LDRT should currently be reserved for refractory clinical phenotypes or implemented strictly within controlled investigational frameworks.